Brilliant X-rays using a two-stage plasma insertion device - Holloway, J; Norreys, P; Thomas, A; Bartolini, R; Bingham, R; Nydell, J; Trines, R; Walker, R; Wing, M (Springer Nature, 2017)
Particle accelerators have made an enormous impact in all fields of natural sciences, from elementary particle physics, to the imaging of proteins and the development of new pharmaceuticals. Modern light sources have advanced many fields by providing extraordinarily bright, short X-ray pulses. Here we present a novel numerical study, demonstrating that existing third generation light sources can significantly enhance the brightness and photon energy of their X-ray pulses by undulating their beams within plasma wakefields. This study shows that a three order of magnitude increase in X-ray brightness and over an order of magnitude increase in X-ray photon energy is achieved by passing a 3 GeV electron beam through a two-stage plasma insertion device. The production mechanism micro-bunches the electron beam and ensures the pulses are radially polarised on creation. We also demonstrate that the micro-bunched electron beam is itself an effective wakefield driver that can potentially accelerate a witness electron beam up to 6 GeV.